Effect of mowing on the structure of sedge communities in the Chwiszczej river valley (Białowieża forest) - Kołos, Aleksander (Quaestiones Geographicae, 2012)
The paper presents the results of the 4-year studies on the influence of mowing on sedge communities structure in the near-edge zone and in the riverbed-adjacent zone of the Chwiszczej River valley (Białowieża Forest). It was assumed that various habitat conditions in different parts of the valley could modify effects of mowing. The floristic richness of sedge dominated patches increases under the influence of mowing in both zones of the valley, mainly as a result of growing number of meadow species. These changes are determined by habitat factors only in the central part of the valley, where ground water’s dynamics is the biggest. Effects of mowing are almost completely canceled by long-lasting flooding. Such flooding may affect on sedge communities’ structure stronger than mowing. Irrespective of local habitat conditions, mowing is favorable to spread of Calamagrostis stricta, which is species of high competitiveness. Its domination could lead to decrease of floristic richness in rush communities.